Materials Data Science Ontology(MDS-Onto): Unifying Domain Knowledge in Materials and Applied Data Science - Balashanmuga Priyan Rajamohan; Alexander C. Harding Bradley; Van D. Tran; Jonathan E. Gordon; Hayden W. Caldwell; Redad Mehdi; Gabriel Ponon; Quynh D. Tran; Ozan Dernek; Jarod Kaltenbaugh; Benjamin G. Pierce; Raymond Wieser; et al. (Scientific Data)
Abstract Ontologies have gained popularity in the scientific community as a way to standardize terminologies in organizations’ data. Although certain cohorts have created frameworks with rules and guidelines on creating ontologies, there exist significant variations in how Materials Science ontologies are currently developed. We seek to provide guidance in the form of a unified automated framework for developing interoperable and modular ontologies for Materials Data Science that simplifies the ontology terms matching by establishing a semantic bridge up to the Basic Formal Ontology(BFO). This framework provides key recommendations on how ontologies should be positioned within the semantic web, what knowledge representation language is recommended, and where ontologies should be published online to boost their findability and interoperability. Two fundamental components of the MDS-Onto framework are the bilingual package called FAIRmaterials for ontology creation and FAIRLinked, for FAIR data creation. To showcase the practical capabilities of FAIRmaterials, we present two exemplar domain ontologies of MDS-Onto: Synchrotron X-Ray Diffraction and Photovoltaics.